2013
DOI: 10.1111/liv.12388
|View full text |Cite
|
Sign up to set email alerts
|

Care of hepatitis C virus infection in France: modifications in three consecutive surveys between 1995 and 2010

Abstract: The care of HCV-infected patients has changed significantly in ‘real life’ through an improvement of pretreatment evaluation before the antiviral introduction and the increased use of antivirals. New HCV therapy combinations including protease inhibitors are warranted to increase the SVR rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
1
Order By: Relevance
“…In France, an observational multicentre study showed an increase in number of newly referred patients with cirrhosis with 7.4% of the patients in 1995, 10.4% in 2001 and 16.1% in 2010. Even though an increase was observed, this percentage in France was lower than in the current study [54]. This is probably due to the fact that, in contrast to the Netherlands as well as many other countries in Europe, France has been actively screening and treating patients over the last two decades.…”
Section: Discussioncontrasting
confidence: 90%
“…In France, an observational multicentre study showed an increase in number of newly referred patients with cirrhosis with 7.4% of the patients in 1995, 10.4% in 2001 and 16.1% in 2010. Even though an increase was observed, this percentage in France was lower than in the current study [54]. This is probably due to the fact that, in contrast to the Netherlands as well as many other countries in Europe, France has been actively screening and treating patients over the last two decades.…”
Section: Discussioncontrasting
confidence: 90%
“…Results from one study site showed HCV viral loads significantly lower than those from the other sites by analysis of variance (ANOVA). That site was in France, where the level of access to antiviral treatment is high; the lower viral loads seen at that site were likely due to higher treatment rates as opposed to a methodological difference (11,12). One drawback of this work was that most samples were tested retrospectively after being frozen, although samples were tested on each platform from the same freezethaw cycle.…”
Section: Discussionmentioning
confidence: 99%
“…New infections mainly occur in active injecting DU, where the estimated incidence is 11.2/100 person-years [ 23 ]. The most frequent genotypes (GT) are GT1 (56–61%), GT3 (19%) and GT4 (9–17%) depending on patient recruitment [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%